Peningkatan Produksi Dan Pemasaran Usaha Ikan Asap Desa Tongo Kec. Bone Pantai Kab. Bone Bolango - Saputra, Dimas Eko; Niode, Idris Yanto; Mendo, Andi Yusniar (Jurnal Ilmiah Wahana Pendidikan, 2024)
Abstract The purpose of this research is to learn more about the development of the smoked fish industry in Tongo village, Bone coast subdistrict. Bolango of bone. This research takes a phenomenological, qualitative approach. This study's data was gathered using a combination of in-person interviews, written records, and informal observations. Reducing data, displaying data, and generating conclusions are the data analysis strategies used in this research. Qualitative descriptive research, in which a specific technique is recorded in order to characterise or describe the status of the item under investigation on the basis of known facts, is what this study is. In addition to the information gathered via interviews, observations, and written records. The findings indicated that Tongo Village produces high-quality smoked fish. This can be seen in several interviews with many consumers who said that the quality of smoked fish in Tongo Village was quite good. even though it has good smoked fish, it still has deficiencies in effectiveness and efficiency in the smoked production process and so does the marketing concept used in the process of selling smoked fish, Tongo village still does not use social media assistance as a marketing tool, where smoked fish sales are still Traditionally, it is marketed in markets and also at street stalls. Suggestions for future study might provide producers valuable insight into how to best use social media for smoked fish promotion. Production and Marketing Improvement, Smoked Fish MSME